Records Management at Universitas Negeri Semarang (Educational Management, 2022)
This study aims to determine the management of static archives at UNNES and the stages of inputting them into the digital archive system. This type of research is qualitative. The focus of this research is the management of static archives, both digitally and manually. The focus of the research is at the State University of Semarang. Data collection techniques include interviews, observation, and documentation studies. The implementation of the power validity checking technique is based on four criteria: degree of trust (credibility), transferability (transferability), dependability (dependability), and certainty (confirmability). Data analysis techniques include data reduction, data presentation, conclusion, and diversification.The research procedure went through four stages: the previous stage of field or pre-field work, fieldwork, data analysis, and report writing. The results of the analysis show that the management of static archives both manually and electronically has not been maximized due to the lack of adequate facilities, including scanners. Besides that, there is no static archive storage, archive depots that are still not organized, so they cannot be arranged properly, and there is no room temperature measurement.